A mononuclear nonheme iron(iii)-peroxo complex binding redox-inactive metal ions - Lee, Yong-Min; Bang, Suhee; Kim, Yun Mi; Cho, Jaeheung; Hong, Seungwoo; Nomura, Takashi; Ogura, Takashi; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Sarangi, Rikimukta; Fukuzumi, Shunichi; Nam, Wonwoo (Chemical Science, 2013)
Redox-inactive metal ions that function as Lewis acids play pivotal roles in modulating reactivities of oxygen-containing metal complexes in a variety of biological and biomimetic reactions, including dioxygen activation/formation and functionalization of organic substrates. Mononuclear nonheme iron(iii)-peroxo species are invoked as active oxygen intermediates in the catalytic cycles of dioxygen activation by nonheme iron enzymes and their biomimetic compounds. Here, we report mononuclear nonheme iron(iii)-peroxo complexes binding redox-inactive metal ions, [(TMC)Fe(O)] -M (M = Sc and Y ; TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane), which are characterized spectroscopically as a 'side-on' iron(iii)-peroxo complex binding a redox-inactive metal ion, (TMC)Fe-(μ, η:η-O)-M (2-M). While an iron(iii)-peroxo complex, [(TMC)Fe(O)], does not react with electron donors (e.g., ferrocene), one-electron reduction of the iron(iii)-peroxo complexes binding redox-inactive metal ions occurs readily upon addition of electron donors, resulting in the generation of an iron(iv)-oxo complex, [(TMC)Fe(O)] (4), via heterolytic O-O bond cleavage of the peroxide ligand. The rates of the conversion of 2-M to 4 are found to depend on the Lewis acidity of the redox-inactive metal ions and the oxidation potential of the electron donors. We have also determined the fundamental electron-transfer properties of 2-M, such as the reduction potential and the reorganization energy in electron-transfer reaction. Based on the results presented herein, we have proposed a mechanism for the reactions of 2-M and electron donors; the reduction of 2-M to the reduced species, (TMC)Fe-(O)-M (2′-M), is the rate-determining step, followed by heterolytic O-O bond cleavage of the reduced species to form 4. The present results provide a biomimetic example demonstrating that redox-inactive metal ions bound to an iron(iii)-peroxo intermediate play a significant role in activating the peroxide O-O bond to form a high-valent iron(iv)-oxo species. © 2013 The Royal Society of Chemistry.